2000
DOI: 10.1063/1.126985
|View full text |Cite
|
Sign up to set email alerts
|

In-plane magnetophotoluminescence studies of modulation-doped GaAs/AlGaAs coupled double quantum wells

Abstract: In-plane magnetic field photoluminescence spectra from a series of GaAs/AlGaAs coupled double quantum wells show distinctive doublet structures related to the symmetric and antisymmetric states. The magnetic field behavior of the upper transition from the antisymmetric state strongly depends on sample mobility. In lower mobility samples, the transition energy shows an N -type kink with fields (namely a maximum followed by a minimum), whereas higher mobility samples have a linear dependence. The former is due t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
(19 reference statements)
1
1
0
Order By: Relevance
“…Therefore, our model is different in this particular way. The disordered potential as a necessary condition for a N-type kink observation was also suggested by Kim et al 15 They have identified this effect in the PL from only one particular sample that had the lowest mobility in the studied set of structures. Samples that allowed the observation of the N-type kink are thus similar to those, where the Fermi edge singularity was studied.…”
Section: Comparison With Theorysupporting
confidence: 69%
See 1 more Smart Citation
“…Therefore, our model is different in this particular way. The disordered potential as a necessary condition for a N-type kink observation was also suggested by Kim et al 15 They have identified this effect in the PL from only one particular sample that had the lowest mobility in the studied set of structures. Samples that allowed the observation of the N-type kink are thus similar to those, where the Fermi edge singularity was studied.…”
Section: Comparison With Theorysupporting
confidence: 69%
“…Similar measurements on wide QWs and heterojunctions have very recently been carried out by Ashkinadze et al 13 Other in-plane magneto-optical measurements, in this case already on symmetric DQW structures, were published by Kim and co-workers. 14,15 In a parallel field, they observed two resolved peaks and their shift to the higher energy with increasing magnetic field. The peaks were related to the recombination of electrons from an upper ͑an-tibonding͒ subband-created by an antisymmetric linear combination of wave functions of a single QW, and from a lower ͑bonding͒ subband formed by a symmetric combination of electron states of a single well.…”
Section: Introductionmentioning
confidence: 99%